2021
DOI: 10.1155/2021/2610122
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Analysis of Antiproliferative Effects of Mouthwashes Containing Alcohol, Sodium Fluoride, Cetylpyridinium Chloride, and Chlorhexidine In Vitro

Abstract: Objectives. In this study, the cytotoxic responses of six different over-the-counter mouthwashes on L929 cells were analyzed by two different techniques: the traditional colorimetric tetrazolium-based reduction assay (MTT) and the modern impedance-based real-time cell analysis (RTCA) system to investigate their biocompatibility in vitro. Thus, the investigation of the antiproliferative effects of the specified materials via different techniques is vital to reach this goal. Materials and Methods. First, L929 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Our results of cytotoxicity by CPC containing mouthrinse and that of pure CPC as assessed by MTS assay that evaluates mitochondrial function indicates that compromised viability might be due to the inhibitory effects of CPC on mitochondrial complex I and mitochondrial O 2 consumption as shown previously [105,106]. An earlier report also showed that a 2 min exposure to CPC containing mouthrinse induced cytotoxicity to an L929 fibroblast cell line [107]. The immediate examination of mouthrinse cytotoxicity after a 2 min exposure was not conducted in our study.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our results of cytotoxicity by CPC containing mouthrinse and that of pure CPC as assessed by MTS assay that evaluates mitochondrial function indicates that compromised viability might be due to the inhibitory effects of CPC on mitochondrial complex I and mitochondrial O 2 consumption as shown previously [105,106]. An earlier report also showed that a 2 min exposure to CPC containing mouthrinse induced cytotoxicity to an L929 fibroblast cell line [107]. The immediate examination of mouthrinse cytotoxicity after a 2 min exposure was not conducted in our study.…”
Section: Discussionsupporting
confidence: 80%
“…The detergent SLS in toothpastes induced comparable cytotoxic effects in primary human keratinocytes from the skin and oral mucosa, suggesting that skin cells could be used as a substitute for oral cells [120]. Furthermore, the use of immortalized human skin keratinocytes (HaCaT cells) or mouse skin fibroblasts (L929 cells) has been common in previous studies that examined toothpastes [82], mouthwashes [107,121], or dental materials [122][123][124][125][126]. Based on these justifications, it can be inferred that utilizing skin melanocytes obtained from a neonatal lightly pigmented donor can serve as a model for oral melanocytes of children.…”
Section: Discussionmentioning
confidence: 98%
“…Mouthwash has been recommended to be the essential for cleaning teeth and gum and freshening the breath. At present, commercial mouthwashes commonly contain some active ingredients including chlorhexidine, cetylpyridonium chloride, fluoride, and alcohol that act as antibacterial substances, however some users may encounter with cytotoxicity and various side effects caused by such active ingredients [24]. In this study, the newly developed antibacterial combination of domiphen and other two non-toxic AMPs namely ɛ-PL and FP was investigated for its inhibitory and bactericidal effects against some oral pathogens, and the mouthwash supplemented with this antibacterial combination in reducing The antimicrobial effects and safety of the efficacy ingredients used in this study have been evaluated in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to its well-documented antibacterial activity, CHX is frequently employed to reduce oral bacterial load [20]. However, mouthwashes containing a high percentage of CHX have been associated with cytotoxic effects in vitro [12,16,44,45]. Therefore, usage of lower concentrations of CHX in combination with CPC have been proposed [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%